Ruby laser hair removal: Evaluation of long-term efficacy and side effects - Valeria B. Campos (2018)
Background and Objective: Although several studies on laser-assisted hair removal have been published, data on long-term follow-up are few. The present study investigated the long-term efficacy and safety of normal-mode ruby laser pulses on hair removal. Study Design/Materials and Methods: The normal-mode ruby laser (Epilaser; 694 nm, 3 msec) was used to treat a wide range of body sites in 51 volunteers. The mean follow-up after the last treatment was 8.37 months. Results: Sixty-three percent of the patients had sparse regrowth. The mean fluence used was 46.5 J/cm2in patients who had sparse hair regrowth and 39.3 J/cm2in patients who had moderate hair regrowth (P = 0.0127). Transient pigmentary changes occurred most frequently in patients with skin type 4. Conclusion: The normal-mode ruby laser is an efficient and safe method for long-term hair reduction, especially in fair- skinned individuals with dark hair. Higher fluences produce greater long-term efficacy. Adverse effects are minimal and transient. (C) 2000 Wiley-Liss, Inc.